P-type transport ATPases in Leishmania and Trypanosoma - Meade John C. (Parasite, 2019)
P-type ATPases are critical to the maintenance and regulation of cellular ion homeostasis and membrane lipid asymmetry due to their ability to move ions and phospholipids against a concentration gradient by utilizing the energy of ATP hydrolysis. P-type ATPases are particularly relevant in human pathogenic trypanosomatids which are exposed to abrupt and dramatic changes in their external environment during their life cycles. This review describes the complete inventory of ion-motive, P-type ATPase genes in the human pathogenic Trypanosomatidae; eight Leishmania species (L. aethiopica, L. braziliensis, L. donovani, L. infantum, L. major, L. mexicana, L. panamensis, L. tropica), Trypanosoma cruzi and three Trypanosoma brucei subspecies (Trypanosoma brucei brucei TREU927, Trypanosoma brucei Lister strain 427, Trypanosoma brucei gambiense DAL972). The P-type ATPase complement in these trypanosomatids includes the P1B (metal pumps), P2A (SERCA, sarcoplasmic-endoplasmic reticulum calcium ATPases), P2B (PMCA, plasma membrane calcium ATPases), P2D (Na+ pumps), P3A (H+ pumps), P4 (aminophospholipid translocators), and P5B (no assigned specificity) subfamilies. These subfamilies represent the P-type ATPase transport functions necessary for survival in the Trypanosomatidae as P-type ATPases for each of these seven subfamilies are found in all Leishmania and Trypanosoma species included in this analysis. These P-type ATPase subfamilies are correlated with current molecular and biochemical knowledge of their function in trypanosomatid growth, adaptation, infectivity, and survival.